2014
DOI: 10.1007/s00268-014-2802-x
|View full text |Cite
|
Sign up to set email alerts
|

1000 Port‐A‐Cath® Placements by Subclavian Vein Approach: Single Surgeon Experience

Abstract: This is a very large series of PAC placement with an ultrasound-guided approach for left subclavian vein and X-ray confirmation, performed by a single surgeon, demonstrating both the safety and effectiveness of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 55 publications
4
48
2
Order By: Relevance
“…In the recent DeliVery for PAH trial (n = 60) intraoperative and perioperative AEs associated with CVC implantation occurred at low rates similar to those observed in our study: the authors reported one case of pneumothorax and three catheter dislocations (all within 1 month of implantation) [16]. In other therapy areas (mainly oncology), intraoperative and perioperative complications associated with CVC implantation have included pneumothorax, accidental arterial puncture, hematoma, dislocations, thrombosis and arrhythmia, and these have varied depending on the implantation protocol [22,23].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the recent DeliVery for PAH trial (n = 60) intraoperative and perioperative AEs associated with CVC implantation occurred at low rates similar to those observed in our study: the authors reported one case of pneumothorax and three catheter dislocations (all within 1 month of implantation) [16]. In other therapy areas (mainly oncology), intraoperative and perioperative complications associated with CVC implantation have included pneumothorax, accidental arterial puncture, hematoma, dislocations, thrombosis and arrhythmia, and these have varied depending on the implantation protocol [22,23].…”
Section: Discussionsupporting
confidence: 77%
“…Repositioning of the catheter led to complete and durable resolution of the arrhythmia. In previous studies, implantation of CVCs or ports led to arrhythmia in 0.2-13.9% of cases; as in our study, repositioning of the catheters caused the arrhythmias to resolve [22,29]. One case of arrhythmia was reported in the DeliVery for PAH trial; however, this occurred before catheter insertion and was resolved by cardioversion [16].…”
Section: Discussionsupporting
confidence: 42%
“…However, establishing a method that avoids both complications and technical failure is a challenge. Existing approaches are associated with both complications and technical failure, even with real-time ultrasound guidance or cephalic vein cut-down [3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients who need TIVADs are already in a fragile state. However, the most common approaches, such as percutaneous puncture methods of the subclavian vein (SCV) or the internal jugular vein (IJV), have the risk of causing serious complications, such as pneumothorax, hemothorax, major nerve injury, catheter pinch-off, or catheter kinking [3][4][5][6][7][8][9][10][11]. The cephalic vein (CV) cut-down technique has been recognized as the safest method and is recently being used more frequently [3,6,12], but, unfortunately, this technique is reported to have a high failure rate (6-30%) [5,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective 7,19,20,25,30,31,33,38,39,41,42,45,50,52,54,56,57,59,61,64 Port sites Chest ports 19,24,31,33,34,36,38,39,42,48,[50][51][52][53][54]57,61,64,68,[73][74][75][76] .702…”
Section: The Ors Of Tivap-associated Vtementioning
confidence: 99%